Re-membering the Black Atlantic : on the poetics and politics of literary memory - Eckstein, Lars. (Amsterdam ; New York : Rodopi, 2006)
The Atlantic slave trade continues to haunt the cultural memories of Africa, Europe and the Americas. There is a prevailing desire to forget: While victims of the African diaspora tried to flee the sites of trauma, enlightened Westerners preferred to be oblivious to the discomforting complicity between their enlightenment and chattel slavery. Recently, however, fiction writers have ventured to 're-member' the Black Atlantic. This book is concerned with how literature performs as memory. It sets out to chart systematically the ways in which literature and memory intersect, and offers readings of.
Illustrations; Introduction; PART I : LITERARY MEMORY; 1 Towards a Poetics of Mnemonic Strategy in Narrative Texts; PART II : MNEMONIC FICTIONS OF THE BLACK ATLANTIC; 2 Caryl Phillips, Cambridge; 3 David Dabydeen, A Harlot's Progress; 4 Toni Morrison, Beloved; Conclusion; Appendix: Source Passages Adapted in Cambridge; Bibliography; Acknowledgements.
Includes bibliographical references (pages 273-289).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Phillips, Caryl -- Criticism and interpretation; Dabydeen, David -- Criticism and interpretation; Morrison, Toni -- Criticism and interpretation; Dabydeen, David; Morrison, Toni; Phillips, Caryl; English literature -- Black authors -- History and criticism; Littérature anglaise -- Auteurs noirs -- Histoire et critique; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature -- Black authors; Englisch; Roman; Sklavenhandel; USA; Englisch; Geschichte 1985-2000; Criticism, interpretation, etc